Modulation of Clock Gene Expression by the Transcriptional Coregulator Receptor Interacting Protein 140 (RIP140) - Poliandri, Ariel H. B. (SAGE Publications, 2011)
Circadian rhythms are generated in central and peripheral tissues by an intracellular oscillating timing mechanism known as the circadian clock. Several lines of evidence show a strong and bidirectional interplay between metabolism and circadian rhythms. Receptor interacting protein 140 (RIP140) is a coregulator for nuclear receptors and other transcription factors that represses catabolic pathways in metabolic tissues. Although RIP140 functions as a corepressor for most nuclear receptors, mounting evidence points to RIP140 as a dual coregulator that can repress or activate different sets of genes. Here, we demonstrate that RIP140 mRNA and protein levels are under circadian regulation and identify RIP140 as a modulator of clock gene expression, suggesting that RIP140 can participate in a feedback mechanism affecting the circadian clock. We show that the absence of RIP140 disturbs the basal levels of BMAL1 and other clock genes, reducing the amplitude of their oscillations. In addition, we demonstrate that RIP140 is recruited to retinoid-related orphan receptor (ROR) binding sites on the BMAL1 promoter, directly interacts with RORα, and increases transcription from the BMAL1 promoter in a RORα-dependent manner. These results indicate that RIP140 is not only involved in metabolic control but also acts as a coactivator for RORα, influencing clock gene expression.